IMAN, SAUDARA, BELARASA (Penelitian Fenomenologis Tentang Radikalisme Agama di Pondok Pasantren Sabilurrosyad Gasek, Karang Besuki, Malang) - Yohanes Fery (Litbang STFT Widya Sasana Malang, 2016)
Religion for human beings is like a sword with two blade-eyes. Religion takes big role for development of human civilization such as promoting values of human dignity, human rights, justice and peaceful living together on the one hand; but religion also appears as the one with antagonistic and destructive eyes on the other. For the sake of religion man can be immediately “moral policeman” who takes surveillance of other persons or even do some unjust things to others especially those who are not in the same line of their beliefs. The existence of radical and fundamental movements proves the “face” of terroristic and unfriendly presence of religion. This is paradox of existence of religion. No religion has ever a destructive doctrine. All of religions pursue peace and justice. This study will deal with “inclusive faith” from the margins of Malang, that is “Pondok Pesantren Sabilurrosyad Gasek, Kelurahan Karang Besuki” (Boarding school Pesantren). To build an inclusive faith becomes sort of alternative way outs to avoid radicalism and fundamentalism of religion. Religious faith does not mean exclusivism. Faith must be inclusivism. The more a person possesses faith the more inclusive and friendly he will be. This research is an attempt of applying phenomenological approach